(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The study aims to measure the relation between job satisfaction and work motivation using primary data collected from 420 teachers working at government polytechnic colleges of Haryana state. It was found from the study that overall job satisfaction was found to cause significant variation in the work motivation level of teachers of government polytechnic colleges. These results are able to corroborate the findings from existing studies in regards to general employee motivation and job satisfaction. It can be concluded from the study that a supportive organizational environment includes developing motivation to work among employees in order for them to feel contentment with their job. Motivated teachers feel more committed towards performing their duties in an educational institution and feel greater sense of satisfaction derived from their work.